Racionalização da construção e a pré-fabricação mista aplicadas à realidade de edifício institucional - Moura, Marcelo de Miranda (2014)
Human activity on Earth has depleted natural resources and caused imbalances that are leading the planet to exhaustion. The building construction has to participate in these proceedings since the withdrawal of the nature feedstock to the impact of construction processes and operation of buildings. It is important that the architecture also gives her contribution to generating friendly alternatives to the planet that causes less impact on their installation and operation. The building must be well established, use materials that allow reuse, refitting or recycling, and finally, has an economic operation grating to natural resources. Thus, we developed a proposal for institutional use building to be built in the Central Campus UFRN, inserted within the limits of Biosciences Center, called Laboratories of Postgraduate CB, to house facilities on research, teaching and information storage. The objective is the development of an architectural design project using the rationalization of construction, modular coordination and prefabricated elements. The result should propose a suitable solution that promotes less impact in the installation of work construction field, quickly and cleanly work and, as adapted to climate, offer comfort to its users, allowing the reduction of energy resources in its operation.